(untitled) (Research, Society and Development, 2020)
Objective: to provide a profile of patient with dizziness complaint in a terciary hospital in Rio Grande do Norte (RN). Methods: 444 medical records were analyzed in a retrospective analytical study, within a quantitative approach, divided into four groups: sex and age (1), characteristics of dizziness (2), comorbidities and risk factors (3) and findings in the physical examination (4). We assign p <0.05 as an indicator of statistical significance Results: of the 444 medical records analyzed, 367 cases were admitted for analysis, 92 of whom were male and 275 female. In addition, most of them reported spinning vertigo (78.3%), lasting for seconds (51%) without association with falling (25.7%) or loss of consciousness (9.3%). The most prevalent etiologies were, Benign Paroxysmal Positional Vertigo (33%), cochlear-vestibular dysfunction (17%) and Menière’s disease (14%). Conclusions: the most frequent profile of patients with dizziness is female, in middle age (median of 52), hypertensive, and Benign Paroxysmal Positional Vertigo is the most prevalent etiology.